Hate is my neighbor - Alibrandi, Tom (Stand Together Publishers, 1999)
"The true story of a community's response to hate. When the Aryan Nations moved its headquarters to Hayden Lake in North Idaho in the late 1970's, the people of Coeur d'Alene and the surrounding area were faced with blatant racism in its midst. This book tells the story of how a community came together around several leaders to stand strong against bigotry and counter the hate that had become its neighbor. The book covers roughly the 1980's, telling the story in novel form but using real incidents, names and places."--Amazon.com.